Affinity [videorecording (DVD)] - O'Neil, Liam; Zaror, Marko, 1978-; Zaror, Marko, 1978-; Zirilli, Daniel; Aguad, Gina; Don, Christopher; Mandylor, Louis; Ence, Brooke; Mirro, Jane (Well Go USA Entertainment, 2025)
Bruno struggles with PTSD, and the former Navy SEAL seeks peace in Thailand. After he rescues a mysterious woman, he finds a new hope for the future and they build a life together. When she is kidnapped, nothing will stop him from finding her, but a shocking truth is uncovered and he must rescue the only thing that's made him feel alive again even if she was never meant to exist.